Research on plantar pressure dynamic distribution characteristics of samba step movements based on biomechanics. Issue 4 (2nd October 2021) - Honglian, Song; Thilak, K. Deepa; Seetharam, Tamizharasi G.
Abstract : Samba dance is a factional part of sports dance. It forms a sports dance system with modern dance. According to the method of sports biomechanics experiment, the dynamic parameters and changing rules of fork foot pressure dynamic distribution characteristics are summarised, which can provide theoretical reference for further study of the basic law of samba dance. From the point of view of sports biomechanics, this paper analyses the rotation of athletes, and combines the knowledge of biomechanics with the rotation characteristics of samba dance. Studies have shown that in the comparison of general parameters, the different indicators of the foot pressure have a certain regularity in different action stages. There were no significant differences between the test group and the control group in terms of walking speed, relative speed, step size, relative step size, foot contact area time, and duration.